2010
DOI: 10.3928/1081597x-20091111-01
|View full text |Cite
|
Sign up to set email alerts
|

Sequential in Vivo Confocal Microscopy Study of Corneal Wound Healing After Cross-Linking in Patients with Keratoconus

Abstract: Although the cornea has no significant tissue modifications clinically after CXL, this study has shown that corneal wounding by riboflavin/UVA collagen CXL induces cellular wound-healing mechanisms and alters the normal structure and cellularity of the cornea for up to 36 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 18 publications
1
28
0
3
Order By: Relevance
“…It has been postulated that these structures represent new synthesized collagens possibly the product of activated keratocytes [17,22,24,25]. Gradual posterior to anterior relocation of these structures has been reported by Kymionis et al during sequential examinations [26].…”
Section: Discussionmentioning
confidence: 92%
“…It has been postulated that these structures represent new synthesized collagens possibly the product of activated keratocytes [17,22,24,25]. Gradual posterior to anterior relocation of these structures has been reported by Kymionis et al during sequential examinations [26].…”
Section: Discussionmentioning
confidence: 92%
“…In vivo studies using confocal microscopy showed similar findings following CXL, with keratocyte loss and stromal edema. In addition, a superficial nerve layer loss was observed [98]. Stromal edema persists for 4-6 weeks and then gradually resolves, with keratocyte repopulation and stromal collagen compaction.…”
Section: Resultsmentioning
confidence: 99%
“…While central stromal keratocyte loss in the treated area persists at 36 months postoperatively, nerve regeneration starts at 1 month and continues past 36 months. A small percentage of patients demonstrate endothelial damage with gradual healing completed at 1 year postoperatively [98]. Collagen fiber diameter increases following CXL, with a reorganization of collagen fibrils in a parallel, lamellar structure similar to a non-KCN cornea (and opposed to a KCN cornea).…”
Section: Resultsmentioning
confidence: 99%
“…All trials have indicated a time-dependence of the effects of CXL, both in terms of transient haze 54 and edema in the early stages, as well as in refractive outcome, which seems to improve over the first year or more following treatment 26,30,31,[51][52] .…”
Section: Effect Of the Treatment On Cornea Claritymentioning
confidence: 99%